A dendritic DPA annihilator—syntheses, photophysical properties and application for co-assembling enhanced triplet-triplet annihilation upconversion. (November 2020) - Guo, Qian; Li, Guojuan; Rao, Ming; Wei, Lingling; Gao, Fanrui; Wu, Wanhua; Yang, Qingshan; Cheng, Guo; Yang, Cheng
Abstract: A dendritic annihilator D-2 containing 18 peripherical methyl ester units was synthesized by attaching the branches on the phenyl unit of 9, 10-diphenylanthracene (DPA). The absorption and emission spectra of D-2 are very similar to the unbranched DPA diacid 5 and the lower branched homolog D-1, while the fluorescence quantum yield increased with the degrees of the branching and was determined to be 86.9% for D-2 in MeOH. D-2 was used as the annihilator for triplet-triplet annihilation upconversion with a Schiff-base Pt(II) complex serving as the sensitizer. It was found that D-2 showed very weak UC emission in MeOH with a UC quantum yield of only 1.4%. Interestingly, the UC emission intensity increased significantly by adding different amounts of water in MeOH, the UC intensity was enhanced by more than 9 fold by adding 40% water into MeOH, and the UC quantum yield was determined to be 10.2% in MeOH with 40% water. A mechanism for the enhancing of UC emission was proposed: When in MeOH, the large molecule size of the dendrimer limited the movability of the acceptor, and the shielding effect of the dendritic branches on the DPA core limited the intimate contacts among DPA cores or between DPA core and the sensitizer. When the water was added, D-2 aggregated to nanoparticles with internal hydrophobic cavities induced by the hydrophobic effect and π-π stacking of DPA core, the sensitizer Pt-1 was captured in the internal hydrophobic cavities, and thus, both the TTET and TTA processes were greatly accelerated which attributed to the enhanced TTA-UC. Graphical abstract: Image 1 Highlights: A dendritic triplet annihilator containing 18 peripherical methyl ester units was designed and synthesized. Efficient UC emission with a FUC  as high as 10.2% was obtained in MeOH aqueous solution. Co-assembling of the sensitizers into the internal cavities of annihilator aggregates is responsible for the high ΦUC .